Control of reproductive floral organ identity specification in Arabidopsis by the C function regulator AGAMOUS. - LOFTUS, BARBARA (My University, 2013)
The floral organ identity factor AGAMOUS (AG) is a key regulator of Arabidopsis thaliana flower development, where it is involved in the formation of the reproductive floral organs as well as in the control of meristem determinacy. To obtain insights into how AG specifies organ fate, we determined the genes and processes acting downstream of this C function regulator during early flower development and distinguished between direct and indirect effects. To this end, we combined genome-wide localization studies, gene perturbation experiments, and computational analyses. Our results demonstrate that AG controls flower development to a large extent by controlling the expression of other genes with regulatory functions, which are involved in mediating a plethora of different developmental processes. One aspect of this function is the suppression of the leaf development program in emerging floral primordia. Using trichome initiation as an example, we demonstrate that AG inhibits an important aspect of leaf development through the direct control of key regulatory genes. A comparison of the gene expression programs controlled by AG and the B function regulators APETALA3 and PISTILLATA, respectively, showed that while they control many developmental processes in conjunction, they also have marked antagonistic, as well as independent activities.
PUBLISHED
Keywords: AGAMOUS